Computational Geosciences Modeling, Simulation and Data Analysis - Wheeler, Mary F.; Dawson, Clint; Yotov, Ivan.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Computational Geosciences publishes high quality papers on mathematical modeling, simulation, numerical analysis, and other computational aspects of the geosciences. In particular the journal is focused on advanced numerical methods for the simulation of subsurface flow and transport, and associated aspects such as discretization, gridding, upscaling, optimization, data assimilation, uncertainty assessment, and high performance parallel and grid computing. Papers treating similar topics but with applications to other fields in the geosciences, such as geomechanics, geophysics, oceanography, or meteorology, will also be considered. The journal provides a platform for interaction and multidisciplinary collaboration among diverse scientific groups, from both academia and industry, which share an interest in developing mathematical models and efficient algorithms for solving them, such as mathematicians, engineers, chemists, physicists, and geoscientists.
Keywords: Earth sciences; Hydrogeology; Geotechnical engineering; Mathematical models; Soil science; Soil conservation; Earth Sciences, general; Geotechnical Engineering & Applied Earth Sciences; Hydrogeology; Mathematical Modeling and Industrial Mathematics; Soil Science & Conservation